GENOME-WIDE ASSOCIATION STUDY FOR GRAIN QUALITY TRAITS IN SPRING BARLEY COLLECTION GROWN IN NORTH KAZAKHSTAN - Genievskaya, Yu.; Almerekova, Sh.; Abugalieva, S.; Abugalieva, A.; Chudinov, V.; Turuspekov, Ye. (Eurasian Journal of Applied Biotechnology, 2023)
Barley is a cereal crop that is grown all over the world. Its grain is used for animal feed, malting, brewing, and food. The quality of barley grain is important, particularly raw starch and protein contents, and it depends on the end-use product. This study looked at a collection of 356 barley accessions from the USA and Kazakhstan grown under conditions of northern Kazakhstan (Karabalyk agricultural experimental station) and genotyped with 1631 polymorphic SNPs markers. The collection was studied for starch (GSC), protein (GPC), cellulose (GCC), and lipids contents (GLC), and for grain test weight (TWL) during two years. Phenotypic analysis demonstrated impact of the year on studied traits and significant associations between grain quality and the yield (P < 0.01). Population structure analysis revealed three subclusters in the studied barley collection with the dominance of the USA’s barley in two of them. As a result of GWAS, 22 significant QTLs (P < 0.001) were identified for the studied grain quality traits including 19 single-trait QTLs, 2 double-trait QTLs, and a one triple-trait QTL. For 16 QTLs, reference quality genes and/or QTLs were found, while the remaining 6 QTLs were presumably novel genetic factors for grain quality traits. As result, these 22 QTLs are expected to be useful for future breeding projects targeting the selection of high grain quality barley cultivars.